2017
DOI: 10.1128/aac.02228-16
|View full text |Cite
|
Sign up to set email alerts
|

Evidence To Support Continuation of Statin Therapy in Patients with Staphylococcus aureus Bacteremia

Abstract: In addition to cholesterol-lowering capabilities, statins possess antiinflammatory and immunomodulatory effects. We sought to quantify the real-world impact of different statin exposure patterns on clinical outcomes in Staphylococcus aureus bacteremia. We conducted a retrospective cohort study among hospitalized patients with positive S. aureus blood cultures receiving appropriate antibiotics within 48 h of culture collection (Veterans Affairs hospitals, 2002 to 2013). Three statin exposure groups were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Obtaining 42% of the isolates in blood samples is alarming because S. aureus bacteremia is associated with high case fatality (20-30%) [19]. All the isolates were penicillin-resistant and sensible to vancomycin, quinupristin/dalfopristin and linezolid (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Obtaining 42% of the isolates in blood samples is alarming because S. aureus bacteremia is associated with high case fatality (20-30%) [19]. All the isolates were penicillin-resistant and sensible to vancomycin, quinupristin/dalfopristin and linezolid (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical data were obtained from the national VA electronic health database that includes International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) diagnostic and procedure codes, chemistry and microbiology data, vital signs, and pharmacy data including bar code medication administration records . This study was approved by the institutional review board and Research and Development Committee of the Providence VA Medical Center.…”
Section: Methodsmentioning
confidence: 99%
“…In a national cohort study by Caffrey et al, it demonstrated in detail that among the patients with Staphylococcus aureus bacteremia, the continuation of statin therapy among pretreated statin users was associated with significant beneficial effects on 30-day hospital mortality, but not in de novo statin users or in pretreated statin users who did not continue statin therapy after admission. [ 17 ] From these studies, it was reasonable to infer that statin therapy should continue for a period up to an effective cumulative dose to exert its protective effects in sepsis. And this is relatively consistent with our study that the protective effect of statins was positively proportional to the cDDDs.…”
Section: Anti-microbial Effectsmentioning
confidence: 99%